THE US WITHDRAWAL AND CHINA’S GROWING ENGAGEMENT IN AFGHANISTAN (Journal of Contemporary Studies, 2023)
China’s interest in Afghanistan has grown substantially over the past few decades. This is evident from the fact that Logar Aynak, the copper extraction project of China, is the largest foreign investment in Afghanistan. In this paper, China’s growing engagement in Afghanistan is studied, especially China’s role in the aftermath of the US withdrawal from Afghanistan is examined at length. The main problems and obstacles China faces in Afghanistan are explored, and challenges and opportunities arise as a result are discussed as well. Considering China’s policy of careful engagement in the region, the nature of China’s growing involvement in Afghanistan is studied.